1999
DOI: 10.1110/ps.8.3.625
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoroethanol‐induced conformational transitions of proteins: Insights gained from the differences between α‐lactalbumin and ribonuclease A

Abstract: The trifluoroethanol (TFE)-induced structural changes of two proteins widely used in folding experiments, bovine alpha-lactalbumin, and bovine pancreatic ribonuclease A, have been investigated. The experiments were performed using circular dichroism spectroscopy in the far- and near-UV region to monitor changes in the secondary and tertiary structures, respectively, and dynamic light scattering to measure the hydrodynamic dimensions and the intermolecular interactions of the proteins in different conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 59 publications
(35 reference statements)
2
60
1
1
Order By: Relevance
“…In contrast, the molar ellipticity of the R9AP-Cter peptide is much smaller in HFIP than in HMeOH (Fig. 2G), which is not consistent with previous observations that this solvent favors the formation of α-helical structures (see section 3.1) [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Circular Dichroism and Infrared Spectroscopy Of The Hydrophocontrasting
confidence: 69%
See 2 more Smart Citations
“…In contrast, the molar ellipticity of the R9AP-Cter peptide is much smaller in HFIP than in HMeOH (Fig. 2G), which is not consistent with previous observations that this solvent favors the formation of α-helical structures (see section 3.1) [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Circular Dichroism and Infrared Spectroscopy Of The Hydrophocontrasting
confidence: 69%
“…Nevertheless, care must be taken when using TFE and HFIP because it is generally believed that they enhance the population of helical conformations of peptides and proteins. In particular, since the pioneering work of Tamburro et al [88], fluorinated alcohols, such as TFE and HFIP, have been shown to promote the formation of α-helices for a large number of proteins and peptides (see, for example, references [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] and the references cited therein). It has been proposed that fluoroalcohol complexes would displace water molecules from the surface of the peptide; the acidity or hydrogen-bonding ability and hydrophobicity of the fluoroalcohols appear to play an important role [104].…”
Section: The Challenge Of Solubilizing Hydrophobic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…β 2 m has a hydrophobic core and is rich in intramolecular hydrogen bonds [19, 20], which favors modification by organic solvents, such as acetonitrile or trifluoroethanol [18, 21]. A detailed study by Heegaard et al [12] and Chiti et al[ 18] proved that I 2 -β 2 m was more amyloidogenic than the N-β 2 m, and treatment with acetonitrile induces a reversible conformational variant of β 2 m, I 2 -β 2 m. This study showed a comparable result.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol destabilizes hydrophobic cores of protein because of its nonpolar character while it enhances secondary-structure formation of protein by minimizing exposure of peptide backbone~Nozaki & Tanford, 1971;Thomas & Dill, 1993;Liu & Bolen, 1995!. These alcohol effects lead to destabilization of the native state of protein and induction of a highly helical denatured conformation~Fink & Painter, 1987;Dyson et al, 1992;Buck et al, 1993;Alexandrescu et al, 1994;Kippen et al, 1994;Shiraki et al, 1995;Kamatari et al, 1996;Hoshino et al, 1997;Gast et al, 1999!. Studies on alcohol effects provide insights into biologically important events because the alcohol solution mimics the environment of biomembrane~Bychkova et al, 1996!, modifies folding pathways of proteins~Lu et al, 1997;Chiti et al, 1999!…”
mentioning
confidence: 99%